Recreational demand in bird sanctuary: the case of Kapar bird sanctuary, Kelang, Malaysia - Amiry, Seddigheh Arab; Yacob, Mohd Rusli; Radam, Alias; Samdin, Zaiton; Shuib, Ahmad (Canadian Center of Science and Education, 2009)
This study investigates the willingness to pay (WTP) for recreational resources at Kapar Bird Sanctuary (KBS), Kelang, Malaysia. The relevant values were estimated by utilizing dichotomous choice form of contingent valuation method (CVM). The logit models were used to analyze the data collected. Open-ended elicitation questions were used to induce respondents to state their maximum WTP, and the OLS model was employed to determine the WTP values. For the purpose of this study, a total 220 respondents were interviewed and asked their WTP for the conservation of KPS as an excitement place for recreational site. The findings of the study showed that the mean willingness to pay ranges from RM12.06 to RM60.94. This study implies that non-use value should be considered in policy making associated with recreational resources. The findings of this study are important in assists policy maker in management and development of recreational sites in Malaysia.